2013
DOI: 10.2340/16501977-1215
|View full text |Cite
|
Sign up to set email alerts
|

Sex-differences in symptoms, disability, and life satisfaction three years after mild traumatic brain injury: A population-based cohort study

Abstract: There are sex differences in outcome 3 years after mild traumatic brain injury. Women and men should be analysed separately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 40 publications
4
29
1
2
Order By: Relevance
“…In mild TBI studies, both sports and nonsports literature report a significant association between female sex, prolonged recovery, 37,38 and postconcussion syndrome 10,34,3943 after mild TBI. Other investigators have found no association between sex and postconcussive complications.…”
Section: Traumatic Brain Injurymentioning
confidence: 98%
See 1 more Smart Citation
“…In mild TBI studies, both sports and nonsports literature report a significant association between female sex, prolonged recovery, 37,38 and postconcussion syndrome 10,34,3943 after mild TBI. Other investigators have found no association between sex and postconcussive complications.…”
Section: Traumatic Brain Injurymentioning
confidence: 98%
“…Discriminating between the effect of sex on postconcussion outcomes, in comparison to other dynamic and confounding variables is difficult; some authors conclude that women and men should be assessed differently after TBI. 10 …”
Section: Traumatic Brain Injurymentioning
confidence: 99%
“…Semistructured interviews are based on flexible guides, which allow for a loose structure of open-ended questions and exploration of the interviewees' attitudes and experiences. Furthermore, semistructured interviews have been used [21][22][23][24][25] to study patients with TBI ranging from adolescents to military personnel and represent an accepted and accurate method of evaluating a phenomenon being studied.…”
Section: Data Collectionmentioning
confidence: 99%
“…Investigations of sex-specific differences in pathology following concussions are needed since data from several studies suggest that males and females are differentially affected by concussions. Females have been shown to suffer more postconcussive pain symptoms including headaches, more cognitive symptoms including visual-spatial deficits, and take longer to recover from post-concussive symptoms [59][60][61]. However, questions remain as to whether the underlying brain pathology is indeed different between men and women with concussion.…”
Section: Avenues For Future Researchmentioning
confidence: 92%